Kinerja Guru PPKn dalam Meningkatkan Nasionalisme Siswa (studi kasus pelaksanaan mata pelajaran PPKn di SMP Negeri 3 Bau-bau) - Nasra, Nasra; Kusumawati, Intan; Paiman, Paiman (Academy of Social Science and Global Citizenship Journal, 2022)
This study aims to determine the learning of PPKn at SMP Negeri 3 Bau-Bau , and to find out the creativity of PPKn teachers at SMP Negeri 3 Bau-Bau in applying nationalism values in PPKn learning. This research is a type of qualitative descriptive research. The data collection techniques used in this study used interview techniques, observations, literature studies, and documentation studies. The data analysis technique used in this study is to use descriptive analysis techniques and infarence analysis. The conclusion produced in this study is that PPKn learning at SMP Negeri 3 Bau-Bau can be said to have been maximized in equipping students about the cultivation of nationalism values as well as understanding nationalism and civic responsibilities such as how to establish harmonious interactions between each other. PPKn learning is also recognized as teaching material that is able to protect students from the entanglement of radicalism. Currently, many of our teenage children are exposed to radicalism and the average of them is still of school age. The suggestions and recommendations in this study are as follows: (1) It is hoped that SMP N egeri 3 Bau-Bau through PPKn learning can maximize the cultivation of Nationalism values to its students, (2) It is hoped that SMP Negeri 3 Bau-Bau will further expand the PPKn learning method with a more straightforward approach so that the students can easily absorb the substance of the PPKn learning, (3) It is hoped that PPKn teachers at SMP Negeri 3 Bau-Bau will be more active in looking for the right learning media when teaching PPKn lessons in class. So as to maximize the cultivation of nationalism values in KDP learning in the classroom, (4) It is hoped that the SMP Negeri 3 Bau-Bau will more regularly encourage workshops on national insights that involve its students. So it is hoped that national insight will become an adhesive element in the interaction between students and students and between teachers and students.